Integration of Augmented Reality (AR) in Learning: An Effort to Promote Elementary Students’ Creative Thinking Skills - Komala Komala; Abdul Rachman Tiro; Retno Wuri Sulistyowati; Lutma Ranta Allolinggi; Ady Akbar (Universitas Pendidikan Mandalika, 2026)
The use of Augmented Reality (AR) in learning has shown rapid development. This study aims to analyze the effect of AR integration on students’ creative thinking abilities in the topic of surface area and volume of cubes and rectangular prisms. We applied a quasi-experimental design by utilizing two existing classes, namely an experimental class consisting of 32 students and a control class consisting of 30 students. We used an essay test instrument measuring creative thinking ability that had undergone expert validation using the Q-Cochran test before being used for data collection. Data analysis was conducted using descriptive statistics and an independent samples t-test. The analysis showed a significant difference between the post-test scores of the two groups, with t(60) = 2.31 and p = 0.012 (one-tailed). The effect size calculation produced a Cohen’s d value of 0.60 (moderate effect). These results indicate that students who participated in AR-assisted mathematics learning obtained higher creative thinking scores than students who participated in learning without AR support. This finding indicates that the implementation of AR is able to provide a meaningful effect as well as a positive contribution to the development of students’ creative thinking abilities in solving mathematics problems.